GC-MS and Antioxidant Capacity Analysis in Propanol Extract of Carthamus Tinctorious L - Indriati, Sri; Yusuf, Muhammad; Riskayanti, Riskayanti; Amaliah, Nur; Latief, Mahyati; Sjafruddin, Rahmiah; Attahmid, Nur Fitriani Usdyana (INTEK: Jurnal Penelitian, 2021)
Safflower, were extracted using propanol solvent at different time intervals: 10, 20, and 30 min at a constant temperature of 40Â°C. The extracts were analyzed by GC/MS technique. The major compounds identified were tetrapentacontane, tetracontane, triacontanol, gamma sitosterol, myristic acid, linoleic acid, stearic acid, palmitic acid, oleic acid, and lauric acid. However, some levels of palmidrol, beta-amyrin, cubenol, and tocopherol were also found in safflower extracts. Most of the volatile compounds were detected between 10â€“30 min time of extraction. The 30 min time of extraction also showed the maximum content of polyphenols and antioxidants in safflower extracts. Thus, 30 min was suggested as the most suitable time for maximum extraction of bioactive volatiles, antioxidants, and polyphenols from Safflower using propanol solvent.